Cor de dentes artificiais de resina acrílica: análise espectrofotométrica das escalas, diferentes lotes e pigmentação por soluções corantes - Catanoze, Isabela Araguê [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The importance of the in the smile is a constant nowadays and it makes patients increasingly demanding, especially with the color of teeth. The aim of this study was to evaluate the color of artificial teeth in acrylic resin three (3) different brands, comparing three (3) different lots of the same model, color and trademark; compare each brand with its color range provided by the manufacturer; and to analyze the color stability of the marks when subjected to immersion in cola, coffee, artificial saliva. For this we used the trademarks Ivostar (Ivoclar Vivadent Ltda), Vivodent PE (Ivoclar Vivadent Ltda) and Tritone (VIPI Industry and Trade Ltd.) and its scales. To compare teeth and scale and between batches of the same brand, 15 teeth of each brand were used, five (5) of each batch, totaling 45 teeth and their respective scales. For the analysis of color stability, teeth 10 of each brand were used a total of 30 teeth were immersed in two (2) liquid foods common to the population (coffee and cola) and artificial saliva. The color readings were taken initially and after 7, 14 and 21 days of storage, and liquid foods replaced daily during the entire storage period. The color measurements were performed using spectrophotometric ultraviolet-visible reflection and the color change (ΔE) were calculated using the CIELab system. The data were submitted to two factors ANOVA followed by Tukey test at 5% significance level to analyze of comparision color of batches and scales. To analyze the color stability after immersion in liquid substances was performed ANOVA repeated four factors medium, followed by Tukey's test at 5% significance level. When comparing the scale and artificial tooth, all brands showed visible difference between the scale and analyzed tooth. As for color stability, all liquid substances used promoted change in color, where the coffee had greater color change capability, followed by artificial saliva and cola

A importância da estética no sorriso é uma constante nos dias atuais, o que torna os pacientes cada vez mais exigentes, especialmente quanto à cor dos dentes. O objetivo deste estudo foi avaliar a cor de dentes artificiais de resina acrílica de três (3) marcas diferentes, comparando três (3) diferentes lotes de mesmo modelo, cor e marca comercial; comparar cada marca comercial com sua escala de cor fornecida pelo fabricante; e analisar a estabilidade de cor das marcas quando submetidos à imersão em refrigerante de cola, café e saliva artificial. Para isto foram utilizadas as marcas comerciais Ivostar (Ivoclar Vivadent Ltda), Vivodent PE (Ivoclar Vivadent Ltda) e Tritone (VIPI Indústria e Comércio Ltda) e suas escalas. Para a comparação entre dentes e escala e entre lotes da mesma marca comercial, foram utilizados 15 dentes de cada marca comercial, sendo cinco (5) de cada lote, totalizando 45 dentes e suas respectivas escalas. Para a análise da estabilidade de cor, foram utilizados 10 dentes de cada marca comercial totalizando 30 dentes, que foram imersas em dois (2) alimentos líquidos comuns à população brasileira (café e refrigerante de cola) e em saliva artificial. As leituras de cor foram realizadas inicialmente e após 7, 14 e 21 dias de armazenagem, sendo os alimentos líquidos substituídos diariamente durante todo o período de armazenagem. A leitura de cor foi realizada por meio de espectrofotometria de reflexão ultravioleta visível e as alterações de cor (ΔE) foram calculadas por meio do Sistema CIELab. Os dados foram submetidos à ANOVA dois fatores seguido de teste de Tukey, com nível de significância de 5% para análise da comparação de cor dos lotes e escalas. Para a análise da estabilidade de cor após a imersão nas substâncias líquidas, foi realizado ANOVA quatro fatores medidas repetidas, seguido de teste de Tukey, com nível...
Keywords: Descoloração de dente; Dente artificial; Espectrofotometria; Cor; Resinas acrílicas; Tooth discoloration